SU KÜLTÜNÜN TÜRKMEN KÜLTÜRÜNDEKİ İZLERİ. - TÖRE, MARAL (Turkish Culture & Haci Bektas Veli Research Quarterly, 2025)
Turkmens believed that the moon, sun, water, wood and some trees had hidden powers in early times. They greeted and talked with these beings, which they considered sacred, and asked for help to protect them from evil. They also made various offerings and sacrifices to ask for victory or to thank them. These elements consecrated by Turkmens did not lose their importance after Islam and continued to live on as folk beliefs. Turkish mythology was formed and shaped around cults such as Ancestors, Earth-Water, Fire, Trees and Animals. According to the belief system adopted by the Turks, each cult has a good. These goodies have protective, helping, healing features as well as punitive features. The traces of the water cult, which contains all these features, are remarkable. The cult of water is based on the beliefs of EarthWater, which was sanctified in Turkish culture before Islam. Today, all beliefs and habits related to water in Turkish tribes are the traces of the cult of Yer-Su in the early period. In this study, the reflections of the water cult in Turkmen folk culture will be mentioned. The information in the research will be determined from the folk beliefs of Turkmens living in Turkmenistan that have survived to the present day. For this reason, some of the information to be given is not available in written sources. However, it will be obtained from the teachings that are known by everyone among the people and have been transmitted since early times. Firstly, words, idioms and proverbs related to water in Turkmen will be emphasised. Then, the beliefs and habits related to the cult of water will be examined. The use of water as a protective, purifying and healing symbol will be mentioned. Thus, the spiritual effects of water in the daily life and thought structure of Turkmens will be observed. Finally, the personalities and auxiliary characters accepted as the pirs of water in Turkmen folk beliefs will be explained. Sacred waters in Turkmenistan and the importance of the national holiday of Suv damcası-altın danesi celebrated every year will be mentioned.